Pengaruh Model Think Pair Share Terhadap Hasil Belajar Peserta Didik Pada Materi Gaya Dan Gerak Di Kelas IV SD Negeri 1 Jagong Jeget Aceh Tengah - Cut Nirmala Hayati; Aida Fitri; Alfiati Syafrina (Universitas Syiah Kuala, 2023)
The purpose of the study was to see the effect of the think pair share model on student learning outcomes in the matter of force and motion in the fourth grade of SD Negeri 1 Jagong Jeget, Central Aceh. The approach used in this research is a quantitative approach. One group pretest post-test design model and quasi-experimental research type. SD Negeri 1 Jagong Jeget as the location of this research was held. Obtaining samples used a purposive sampling technique. Using a sample of 16 fourth-grade students consisting of 7 boys students and 9 girls students. Collection data was carried out by giving a test technique with a total of 20 multiple choice questions before 3 meetings to get student learning outcomes. The data analysis technique in this study used a t-test at a significant level of 0.05 before the test was fulfilled. From the results of the study, it was found that 1) improving student learning outcomes after obtaining learning with the think pair share model 2) learning outcomes of students who received learning with the think pair share model were very good when compared with students who had learning experiences 3) students were very both active in the learning process using the think pair share model when compared to lessons that do not use the think pair model, students tend to be bored and do not have the enthusiasm to learn. The application of the think pair share model in learning is proven to be able to produce better student learning outcomes on force and motion material.